Gold Nanocluster-Encapsulated Hyperbranched Polyethyleneimine for Selective and Ratiometric Dopamine Analyses by Enhanced Self-Polymerization - Zhang, Jing; Liu, Ying; Liu, Yang; Liu, Wencai; Lu, Fengniu; Yuan, Zhiqin; Lu, Chao (Frontiers in Chemistry, 2022)
The exploitation of selective and sensitive dopamine (DA) sensors is essential to deep understand its biological function and diagnosis of related diseases. In this study, gold nanocluster-encapsulated hyperbranched polyethyleneimine (hPEI-Au NCs), has been explored as the specific and ratiometric DA nanoprobe through hPEI-assisted DA self-polymerization reaction. The Au NCs encapsulation not only provides a fluorescent internal reference, but also enhances the DA self-polymerization by weakening the proton sponge effect of hPEI layer. Rapid and sensitive DA detection is realized through the proposed hPEI-Au NC nanoprobe with a limit of detection of 10 nM. The favourable selectivity over other possible interferents including amino acids, sugars and salts is due to the specific self-polymerization reaction. The DA analysis in urine samples with small relative standard deviations has been accomplished with hPEI-Au NC nanoprobe.